Decadal trends in global pelagic ocean chlorophyll: A new assessment integrating multiple satellites, in situ data, and models - Gregg, Watson W.; Rousseaux, Cécile S. (Journal of geophysical research. Oceans, 2014)
Quantifying change in ocean biology using satellites is a major scientific objective. We document trends globally for the period 1998–2012 by integrating three diverse methodologies: ocean color data from multiple satellites, bias correction methods based on in situ data, and data assimilation to provide a consistent and complete global representation free of sampling biases. The results indicated no significant trend in global pelagic ocean chlorophyll over the 15 year data record. These results were consistent with previous findings that were based on the first 6 years and first 10 years of the SeaWiFS mission. However, all of the Northern Hemisphere basins (north of 10° latitude), as well as the Equatorial Indian basin, exhibited significant declines in chlorophyll. Trend maps showed the local trends and their change in percent per year. These trend maps were compared with several other previous efforts using only a single sensor (SeaWiFS) and more limited time series, showing remarkable consistency. These results suggested the present effort provides a path forward to quantifying global ocean trends using multiple satellite missions, which is essential if we are to understand the state, variability, and possible changes in the global oceans over longer time scales. Key Points Global ocean pelagic annual median chlorophyll shows no significant trend Northern Hemisphere basins exhibit significant declining trends Bias correction and data assimilation enable trend detection using two sensors